Fish Farmer’s Attitude Based on Production Risk of Tiger Grouper, Epinephelus fuscoguttatus Growing in Floating Net Cages in Lampung Gulf - Tajerin Tajerin (Jurnal Perikanan Universitas Gadjah Mada, 2007)
This study was aimed to investigate fish farmer’s attitude on production risk of Epinephelus fuscoguttatus growing in floating net cages, and to evaluate the impact of input usage on the production risk. The production risk explicitly assumed, reflected in the variability of E. fuscoguttatus production.The study used the case of fish farmer’s production of grouper growth out in floating net cages in Lampung Gulf, Lampung Province as an analysis unit. The respondent of fish farmers were obtained by census method.The analysis result suggested that the fish farmers were risk-averters toward fish seed, fish feed and human labor input. It also appeared that fish seed and fish feed were risk-inducing inputs while the amount of human labour was a risk-reducing input. Fish farmer’s attitude that avoid of the usage of human labour, more considered by decreased effort efficiency which was affected by increasing the amount of human labor whereas production level tend to remained or lower. However by the level domination of adequate E. fuscoguttatus culture technique which owned by the human labour, the usage of human labor could be act as “risk-reducing”.